Extrathymic CD4+CD8+ lymphocytes in Chagas disease: Possible relationship with an immunoendocrine imbalance - Perez, Ana Rosa (2012)
Double positive CD4+CD8+ (DP) T cells normally represent a thymic subpopulation that is developed in the thymus as precursors of CD4+ or CD8+ single-positive T cells. Recent evidence showed that DP cells could be also tracked in secondary lymph organs showing an activated phenotype. The detection of DP activated population in the periphery that bears T cell receptors unselected during the thymic negative selection of either murine models of Trypanosoma cruzi infection and similar findings in human with Chagas disease raise new questions about the relevance of this population in the pathogenesis of this major parasitic disease and their possible links with immunoendocrine alterations.